Pathogenic variability in Tilletia indica, the casual agent of Karnal bunt of wheat - R. AGGARWAL and K.D. SRIVASTAVA, P.P. THIRUMALAISAMY, D.V. SINGH*, (Indian Phytopathology, 2006)
Twenty isolates of Tilletia indica collected from disease prevailing North and North-western area of India showed pathogenic variations on eighteen host differentials. Three distinct aggressive types were identified as Karnal bunt Aggressive type viz. KB-Ag I, KB-Ag II and KB-Ag III. Isolate collected from Kashipur (KB17) was the most aggressive as it produced susceptible reaction on most of the host differentials. Isolates collected from Gurdaspur (KB5), Kapurthala (KB6), Faridkot (KB7), Sangrur (KB8), Bareilly (KB15) and Hardoi (KB16) matched their aggressiveness with KB17 and were grouped as KB-Ag I. Isolates collected from Narwana (KB1), Karnal (KB2), Samalkha (KB4), Ambala (KB13), Hoshiarpur (KB10), Ludhiana (KB9), Hapur (KB3), Pantnagar (KB12) and Delhi (KB14) were similar in their aggressiveness on host differentials and grouped as KB-Ag II. Four isolates belonging to Jammu (KB18), Bilaspur (KB11), Solan (KB20) and Almora (KB19) were least aggressive and grouped as KB-Ag III.